Front Cover. (27th March 2019) - Cingolani, Andrea; Zanotti, Valerio; Zacchini, Stefano; Massi, Massimiliano; Simpson, Peter V.; Maheshkumar Desai, Nima; Casari, Ilaria; Falasca, Marco; Rigamonti, Luca; Mazzoni, Rita
Abstract : The cover image is based on the Full Paper Synthesis, reactivity and preliminary biological activity of iron(0) complexes with cyclopentadienone and amino‐appended N‐heterocyclic carbene ligands by Andrea Cingolani et al., https://doi.org/10.1002/aoc.4779 . Illustration Credit: Rita Mazzoni and Elena Gigli.